Fulfilling the Right to Have a Family and Continuing Offspring: Different Religious Marriage’s Case - Surjanti Surjanti; Haris Yudhianto; M. Sri Astuti Agustina; Retno Sari Dewi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The focus of this research is on the existence of marriage as a prerequisite for the right to have a family and continuing offspring based on an analysis of the ratio decidendi of the Constitutional Court (MK) Decision No. 24/PUU-XX/2022 (MK Decision of Different Religions 2022). This research is normative legal research prioritizing a case, concept, and statutory approach. The results of the study confirm that the existence of marriage in the ratio decidendi of the MK Decision of Different Religions 2022 places marriage in two aspects, namely: the aspect of mandatory prerequisites and the aspect of the role of state regulation. As a mandatory prerequisite, marriage is an essential aspect of realizing the right to have a family and continue offspring.The dimension of marriage as a prerequisite for the realization of the right to have a family and continue offspring in the ratio decidendi of the MK Decision of Different Religions 2022 emphasizes two aspect. First, marriage is a prerequisite and not a right, which means that marriage cannot be carried out freely and at will. Second, marriage has a close relationship with religious law, which means that in carrying out marriage as a prerequisite for the realization of the right to have a family and continue offspring, it is necessary to base the laws of each religion and the beliefs held by the community.